Use of Subsurface Geology in Assessing the Optimal Co-Location of CO2 Storage and Wind Energy Sites - I. de Jonge-Anderson; J. R. Underhill (Earth Science, Systems and Society)
Opportunities exist to re-purpose depleted gas fields in the Southern North Sea as CO2 storage sites if, where and when they meet the right set of geological, engineering, and non-technical criteria. Fields positioned on the western edge of the basin are attractive as they lie close to the major industrial emitters of East England which need to decarbonise if the UK’s Net Zero targets are to be met. Having stopped production in 2018, Pickerill has CO2 storage potential as it is a proven trap from which around 440 Bcf of gas has been produced and it is located near the coastline. We use a public-domain 3D seismic dataset, wireline logs, core reports and production data to assess its CO2 storage potential. The Rotliegend Group reservoir (Leman Sandstone Formation) is a mixed aeolian/fluvial succession with variable thickness (25 m–80 m), high net-to-gross (0.9–1.0), moderate average porosity (9%–17%) and fair-average permeability (>1 mD). The seal is Zechstein Group evaporites and carbonates which thin and swell in response to their post-depositional mobility (halokinesis), further affecting and deforming the overburden. The structure is defined to the south by a WNW-ESE-striking fault system, but the north of the field is characterised mostly by dip closure of the reservoir. NW-SE-striking faults transect the field and segment the structure into several compartments, three of which appear particularly good candidates for CO2 storage and have a combined CO2 storage capacity of 32 MtCO2. If combined with nearby satellite fields, there is potential for the development of a CO2 storage cluster capable of sequestering 60 MtCO2, however, this potential is challenged by the planned development of an offshore wind farm. Turbines fixed to the seabed over the field would restrict where new CO2 injection wells might be drilled and efforts to measure, monitor and verify the CO2 plume using conventional towed-streamer seismic. There is an urgent need to resolve the competition for offshore acreage to ensure that attractive CO2 storage sites like Pickerill are not disadvantaged but can play a full part in complementing alternative renewable energy sources within the energy transition.